Hizbul Wathan Bagi Pendidikan Kemandirian Tingkat Sekolah Dasar - Wiranthi Prastomo; Muhiyatul Huliyah; Moh. Nasrudin; Intan Kusumawati; Nuryati Nuryati; A.N. Ari Bowo (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2019)
This study aims to describe self-reliance education through HW activities at the athfal level in one of Muhammadiyah elementary schools in Yogyakarta. In planting an independent character, it is certainly typical of Scouts when it refers that both of them have differences and similarities in scouting. The relationship between the supervisor and the standby participant is like the relationship between educators and students who refer to the Quran as the main guideline for Islam as the main focus in HW. This qualitative paradigm field research was by directly observing the implementation of HW extracurricular activities at the Athfal level at the Muhammadiyah Primary School in Serut, Bantul district. With the materials and methods of implementing existing activities, the independence education in Hizbul Wathan Extracurricular activities at SD Muhammadiyah Serut is in line with Law no. 20 of 2003 concerning the National Education System that the function of education is to develop religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by students, society, nation and state.